Perancangan Sistem Monitoring Ketinggian Air Sebagai Pendeteksi Banjir Berbasis IoT Menggunakan Sensor Ultrasonik - Nicko Pratama; Ucuk Darusalam; Novi Dian Nathasia (STMIK Budi Darma, 2020)
High rainfall in the rainy season can last about six months, this makes it rain continuously and cause an increase in the volume of water that has the potential for flooding. While the public does not get information or notice directly when it will happen. To anticipate these problems, the design of a water level monitoring system as an early flood detection based on IoT is considered efficient. The system will detect the distance of the sensor to the surface of the water, if the distance of the surface water approaches the sensor, the system will sound the siren as a sign of flooding. The system will display the alert status that occurs and the water surface distance in realtime.. From 100 data of water surface distance with ultrasonic sensors that have been tested, get 6 times the distance reading error. In testing of several water surface distances with sensors, the system can store all distance data into a database.